Second Human Pegivirus in Hepatitis C Virus–Infected and Hepatitis C Virus/HIV-1–Co-infected Persons Who Inject Drugs, China - Haiying Wang; Zhengwei Wan; Qiang Sun; Nalin Zhu; Tianyi Li; Xuqi Ren; Xiaoping An; Shuyun Deng; Yue Wu; Xiufen Li; Lin Li; Jingyun Li; et al. (Emerging Infectious Diseases, 2018)
We report the presence of the second human pegivirus (HPgV-2) in Guangdong and Sichuan Provinces in China. The prevalence of HPgV-2 in hepatitis C virus/HIV-1–co-infected persons who inject drugs was 12.9% in Guangdong and 15.9% in Sichuan. This population is at high risk for HPgV-2 infection.